Effects of Salacia oblonga on aluminium induced changes in membrane ATPases in brain cortex and hematological parameters in Wistar albino rats - C. M., Divyashanthi; A., Nandhini; Datchanamurty, Barathane (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The current study was done to evaluate the effect of hydro alcoholic extract of Salacia oblonga on aluminum induced toxicity in brain cortex and blood in Wistar albino rats. Methods: The experimental animals were divided into four groups, each group comprising of six animals for 36 days of experimental duration. We investigated Na+/K+, Mg2+, Ca2+ ATPases enzyme activity in brain cortex and hematological changes if any, upon administration of aluminum chloride (Alcl3) (300 mg/kg b.w), hydro alcoholic extract of Salacia oblonga (67 mg/kg b.w) and Alcl3+ Salacia oblanga with control (distilled water). Results: In brain cortex, Salacia caused an increased in activity of ATPases. Combined administration of Salacia suppressed the influence of aluminum on the ATPases in the brain cortex (p<0.05). Both aluminum as well as Salacia did not cause any alteration in the hemoglobin content of blood in Wistar albino rats. The erythrocytes count was also not altered by treatment with either aluminum or Salacia. Combined treatment with Salacia suppressed the influence of aluminum with reference to neutrophil count and significant increases in monocyte as well as lymphocyte count were seen. Thus, repeated administration of aluminum causes a decrease in neutrophil and increase in lymphocyte count. Conclusions: All the ATPases in brain cortex were found to be affected by aluminum administration and Salacia is found to counteract the ATPase effect to a particular extent implying the presence of an active principle that can counteract the aluminium toxicity indicating its possible usefulness in aluminum toxicity.